Identifying Archetypes of an Enhanced System Dynamics Causal Loop Diagram in Pursuit of Strategies to Improve Smallholder Beef Farming in Java, Indonesia. (22nd August 2014) - Setianto, Novie Andri; Cameron, Donald; Gaughan, John B.
<x xml:space="preserve">Abstract</x> In the body of systems thinking, system dynamics (SD) is considered to be a powerful tool. However, when dealing with a social entity such as a smallholder group, SD is considered to be a researcher‐centrist methodology that may not accurately reflect perspectives and social power sensitivities of all stakeholders. This paper reports on research in which, in an effort to enhance SD, these deficiencies are addressed through complementary application of soft systems methodology, which has strength in acknowledging multiple perspectives, and critical systems heuristics, which can explicitly address power asymmetry. A series of interviews and workshops was undertaken to identify the problematic situation of smallholder beef farming in Java. To describe its linkages, this problematic situation was then translated into a causal loop diagram from which the systems archetypes were identified. The nature of each archetype is described, and the implications for identification of the possible system leverage points are discussed. Copyright © 2014 John Wiley & Sons, Ltd.